The moral foundations of cryptocurrency: evidence from Twitter and survey research - Banker, Sachin; Park, Joowon; Chan, Eugene Y. (Frontiers in Psychology, 2023)
Despite its relatively brief history, cryptocurrency has already had a profound impact on the economy, with some predicting that it will eventually replace traditional fiat currencies.Historically, it had dark associations with illegal activities in the early days, although perceptions and associations likely have, in recent years, changed for the better. Thus, understanding how people perceive the morality of cryptocurrency currently forms the motivation of the current research. We, in particular, examine associations dependent on political ideology. Across both a large-scale analysis of Twitter posts (N = 959,393) and controlled survey research (N = 487), we find that cryptocurrency is currently best understood as being more strongly linked to conservative vs. liberal moral foundations. Cryptocurrency-related posts were more likely to express conservative moral foundations (Authority, Purity, Loyalty) rather than liberal moral foundations (Fairness, Care), and individual endorsement of these conservative moral foundations was associated with increased interest in crypto investment.